IN VITRO ANTIOXIDANT POTENTIAL OF ETHYL ACETATE FRACTION OF SEED OF EUGENIA JAMBOLANA - JANA, KISHALAY; GHOSH, ABHINANDAN; Ghosh, Debidas (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Over production of reactive oxygen species is dangerous for all living organisms which can damage the key cellular constituents such as protein, lipid, and DNA. Recently, searching of different new plant sources having free radical scavenging activity is an interesting field of research in the pharmaceutical area, as natural products are harmless and low cost. In this connection, we focused to evaluate the antioxidant potential of ethyl acetate fraction of seed of Eugenia jambolana (E. jambolana) using different in vitro tests. Methods: To assess the antioxidant activity, said fraction was examined on scavenging of hydrogen peroxide, hydroxyl radical scavenging potential, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging effect, and anti-lipid peroxidation activity by biochemical methods. We also measured total phenol and flavonoids contents in the said fraction. Results: Results indicated that ethyl acetate fraction has strong scavenging activity on hydroxyl radical with inhibitory concentration (IC50) value 54.34 Î¼g/ml, hydrogen peroxide with IC50 value 63.25 Î¼g/ml, DPPH radical with IC50 value 154.95 Î¼g/ml and the said fraction also showed remarkable inhibition in lipid peroxidation having IC50 value 59.42 Î¼g/ml. In another phytochemical study focused that the fraction is rich in phenolic compounds (18.54 mg gallic acid equivalent/g dried extract) and flavonoids (122.32 Î¼g quercetin equivalent/g dried extract). Conclusion: The findings indicated that the ethyl acetate fraction of seed of E. jambolana is a rich source of natural antioxidants. Keywords: Antioxidant, Eugenia jambolana, Free radicals, Lipid peroxidation.